Differential translocation of the fatty acid transporter, FAT/CD36, and the glucose transporter, GLUT4, coordinates changes in cardiac substrate metabolism during ischemia and reperfusion. - Heather, L; Pates, K; Atherton, H; Cole, M; Ball, DR; Evans, R; Glatz, J; Luiken, J; Griffin, J; Clarke, K (2013)
BACKGROUND: Fatty acid and glucose transporters translocate between the sarcolemma and intracellular compartments to regulate substrate metabolism acutely. We hypothesised that during ischemia fatty acid translocase (FAT/CD36) would translocate away from the sarcolemma to limit fatty acid uptake when fatty acid oxidation is inhibited. METHODS AND RESULTS: Wistar rat hearts were perfused during preischemia, low-flow ischemia, and reperfusion, using (3)H-substrates for measurement of metabolic rates, followed by metabolomic analysis and subcellular fractionation. During ischemia, there was a 32% decrease in sarcolemmal FAT/CD36 accompanied by a 95% decrease in fatty acid oxidation rates, with no change in intramyocardial lipids. Concomitantly, the sarcolemmal content of the glucose transporter, GLUT4, increased by 90% during ischemia, associated with an 86% increase in glycolytic rates, 45% decrease in glycogen content, and a 3-fold increase in phosphorylated AMP-activated protein kinase. Following reperfusion, decreased sarcolemmal FAT/CD36 persisted, but fatty acid oxidation rates returned to preischemic levels, resulting in a 35% decrease in myocardial triglyceride content. Elevated sarcolemmal GLUT4 persisted during reperfusion; in contrast, glycolytic rates decreased to 30% of preischemic rates, accompanied by a 5-fold increase in intracellular citrate levels and restoration of glycogen content. CONCLUSIONS: During ischemia, FAT/CD36 moved away from the sarcolemma as GLUT4 moved toward the sarcolemma, associated with a shift from fatty acid oxidation to glycolysis, while intramyocardial lipid accumulation was prevented. This relocation was maintained during reperfusion, which was associated with replenishing glycogen stores as a priority, occurring at the expense of glycolysis and mediated by an increase in citrate levels.